2008
DOI: 10.1007/s00244-008-9229-z
|View full text |Cite
|
Sign up to set email alerts
|

Lincomycin and Spectinomycin Concentrations in Liquid Swine Manure and Their Persistence During Simulated Manure Storage

Abstract: Antimicrobials administered to livestock can be excreted up to 75% in the feces and urine. Liquid swine manure from confined animal feeding operations is generally retained in lagoon storage until it is applied as a nutrient source to crop and pasture land. Thus, the applied manure becomes a possible source of antimicrobials to aquatic ecosystems. In the prairie region of Canada, lincomycin and spectinomycin are two antimicrobials that are frequently administered to pigs for prevention of post-weaning diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Due to the widely use of antibiotics in treating disease, protecting animal health and improving the feeding efficiency of animals, some of the antibiotics via the manure application were imported in soils and been strongly adsorbed (Sarmah et al, 2006;Martínez-Carballo et al, 2007;Aust et al, 2008). Further, soil antibiotics can be transported to surface and ground water, and also can be taken up by plants (Kuchta and Cessna, 2009). The spatial distributions of soil antibiotics are complex, because they are all from the external sources, and have irregular transportation into water and the irregular absorption by different plants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the widely use of antibiotics in treating disease, protecting animal health and improving the feeding efficiency of animals, some of the antibiotics via the manure application were imported in soils and been strongly adsorbed (Sarmah et al, 2006;Martínez-Carballo et al, 2007;Aust et al, 2008). Further, soil antibiotics can be transported to surface and ground water, and also can be taken up by plants (Kuchta and Cessna, 2009). The spatial distributions of soil antibiotics are complex, because they are all from the external sources, and have irregular transportation into water and the irregular absorption by different plants.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect measurements suggest that 40–90% of administered antibiotics are eliminated from animal body via feces or urine, excreted either as the parent compound or as metabolites [7]. Excreted antibiotics can persist in the environment and, even at very low concentrations, can cause emergence of antibiotic resistance in soil microorganisms, leading to dissemination of antibiotic resistance to humans and animals [8][11]. Therefore, reliable quantification of antibiotics excreted in feces and urine is needed assess the environmental impact of the livestock industry.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that a high concentration (7820 ng/mL) of lincomycin could be detected in liquid manure of swine following administration in feed. In liquid manure, ~84% of the lincomycin was in the dissolved phase, and 16% was associated with the solid components of the manure (Kuchta and Cessna, 2009b). Additionally, lincomycin could be detected in lagoon manure over a period of 5 months when applied as an amendment to agricultural land.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lincomycin could be detected in lagoon manure over a period of 5 months when applied as an amendment to agricultural land. When livestock manure from CAFOs is used as liquid fertilizer, antibiotics may transport to surface and ground water, as well as soil, and act as a reservoir (Hornish et al, 1987; Kuchta and Cessna, 2009b; Kwon, 2011). Therefore, lincomycin is one of the antibiotics that could easily accumulate in the environment adjacent to CAFOs (Hu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%